Moderation In The Qur’an: Building Pluralism Through The Principle Of Wasatiyyah (Case Study Of Surah Al-Hujurat 49:13) - Sayaka, Labibah Sayaka Ilma; Rahayu, Indah; Rahmawati, Kiki Anita; Tolchah, Moch; Almalouh, Awashah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study examines the value of moderation (wasatiyyah) in the Qur’an as a foundation for building pluralism, using Surah Al-Hujurat verse 13 as the main reference. The objective is to explore how the principle of wasatiyyah contributes to fostering social harmony in a diverse society. Employing a qualitative method with a literature review and tafsir analysis, the study finds that religious moderation plays a crucial role in countering extremism and radicalism. It also promotes inclusive interfaith dialogue and mutual respect. The findings highlight that diversity, when managed with the value of wasatiyyah, becomes a source of unity rather than division. This makes moderation a strategic approach to achieving peace and justice in society.